In Youth Developing the Skills of Fighting Against Popular Culture is the Challenging Problem of Today - Miralieva Dilafruz; Musakhanova Gulnora; Ochilova Gulnoza (Zien Journals, 2023)
In the article, the author examines the problems of today's children and the formation of their skills in sorting information.
Keywords: Mass culture; popular culture; spiritual threats; information security